In Adult Rats With Polycystic Ovarian Syndrome, Unilateral or Bilateral Vagotomy Modifies the Noradrenergic Concentration in the Ovaries and the Celiac Superior Mesenteric Ganglia in Different Ways - Linares, Rosa; Rosas, Gabriela; Vieyra, Elizabeth; Ramírez, Deyra A.; Velázquez, Daniel R.; Espinoza, Julieta A.; Morán, Carolina; Domínguez, Roberto; Morales-Ledesma, Leticia (Frontiers in Physiology, 2019)
In rats with polycystic ovarian syndrome (PCOS), induced by estradiol valerate (EV) injection, the sectioning of the vagus nerve restores ovulatory function; suggesting that the vagus nerve stimulates the onset and development of PCOS. We analyzed whether the role played by the vagus nerve in PCOS development is associated with the nerves' regulatory role of noradrenergic activity in the celiac-superior mesenteric ganglion (CSMG). Ten-day-old rats were injected with corn oil (Vh) or EV (2 mg). At 76-days of age, rats injected with Vh or EV were submitted to sham-surgery or the sectioning of one or both vagus nerves (vagotomy). The animals were sacrificed at 80-82 days of age at vaginal estrus smear. Compared to Vh-treated animals, EV-induced PCOS rats showed a lack of ovulation, the presence of follicular cysts, and a high concentration of testosterone, without changes in noradrenaline concentrations in the CSMG or ovaries. In PCOS rats, sham-surgery lowered testosterone and noradrenaline concentrations in the CSMG but did not restore ovulation. In animals with PCOS, the vagotomy lowered testosterone concentrations to a larger degree than in sham-surgery animals. The ovaries of rats with PCOS and vagotomy showed fresh luteal corpus, indicating ovulation. In EV-treated rats with unilateral vagotomy, the concentration of noradrenaline in the CSMG was similar to rats with PCOS and sham-surgery, which did not ovulate, while in the ovaries of PCOS rats with left or bilateral vagotomy the noradrenaline concentration was lower than in sham-surgery treated animals. Our results suggest that the vagus nerve regulates PCOS development through a different mechanism than the increase in the monoaminergic activity in the CSMG and the ovaries.